Uprooting Bias in the Academy Lessons from the Field - Bisson, Linda F.; Grindstaff, Laura; Brazil-Cruz, Lisceth; Barbu, Sophie J. (Springer Nature, 2022)
This open access book analyzes barriers to inclusion in academia and details ways to create a more diverse, inclusive environment. It describes the implementation of UC Davis ADVANCE, a grant program funded by the National Science Foundation, to increase the hiring and retention of underrepresented scholars in the STEM fields (science, technology, engineering and mathematics) and foster a culture of inclusion for all faculty. It first describes what the barriers to inclusion are and how they function within the broader society. A key focus here is the concept of implicit bias: what it is, how it develops, and the importance of training organizational members to recognize and challenge it. It then discusses the limitations of data collection that is guided by the convention assumption that being diverse automatically means being inclusive. Lastly, it highlights the importance of creating a collaborative, interdisciplinary, and institution-wide vision of an inclusive community.